Sleep Disorders in Methadone Maintenance Treatment Volunteers and Opium-dependent Patients - Khazaie, Habibolah (Addict Health, 2016)
BACKGROUND: The relationship between substance use and sleep is bidirectional. Substance use directly causessleep disturbances, and sleep problems are a critical factor in substance-use relapse. METHODS: This study evaluated sleep disorders in 65 methadone maintenance treatment (MMT) patients, and61 opium-dependent patients who did not receive any treatment between September 2011 and July 2012 inKermanshah, Iran. Both groups filled out the Pittsburgh Sleep Quality Index (PSQI) and Global SleepAssessment Questionnaire (GSAQ). FINDINGS: Sleep disorders were remarkably similar in both groups: 78.5% of MMT patients and 87.7% ofopium-dependent patients suffered from sleep problems. Sleep disorders in the opium-dependent groupwere remarkably higher and more prominent. CONCLUSION: Compared to opium, MMT does not have as many negative effects on sleep and is more effectivein mitigating sleep problems.